2003
DOI: 10.1109/tnsre.2003.810431
|View full text |Cite
|
Sign up to set email alerts
|

A miniaturized neuroprosthesis suitable for implantation into the brain

Abstract: This paper presents current research on a miniaturized neuroprosthesis suitable for implantation into the brain. The prosthesis is a heterogeneous integration of a 100-element microelectromechanical system (MEMS) electrode array, front-end complementary metal-oxide-semiconductor (CMOS) integrated circuit for neural signal preamplification, filtering, multiplexing and analog-to-digital conversion, and a second CMOS integrated circuit for wireless transmission of neural data and conditioning of wireless power. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 5 publications
0
30
0
1
Order By: Relevance
“…Recently, the parallel recording of signals from many sites has become feasible, allowing examination of the behaviour of whole cell populations. Massive parallel recording from neurons has been reported using micro-electromechanical (MEMS) electrode arrays [37], on-chip electrodes [41] and micromachined probes [16,30]. In nerve signal (ENG) recording the multi-electrode cuff has been introduced to record signals at many locations as they propagate along the nerve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the parallel recording of signals from many sites has become feasible, allowing examination of the behaviour of whole cell populations. Massive parallel recording from neurons has been reported using micro-electromechanical (MEMS) electrode arrays [37], on-chip electrodes [41] and micromachined probes [16,30]. In nerve signal (ENG) recording the multi-electrode cuff has been introduced to record signals at many locations as they propagate along the nerve.…”
Section: Introductionmentioning
confidence: 99%
“…Time-interleaved multiplexers typically follow preamplification of the signal [7,9,14,16,25,30,37,38]. This placement is ideal for low-noise recording as discussed in Sect.…”
Section: Introductionmentioning
confidence: 99%
“…The latter media are used for creation of the eye-prosthesis (so called the "silicon eye"). The medium suggested can serve as the prosthesis prototype for perception of the color images [9][10][11][12][13][14][15].…”
Section: The Object Of the Studymentioning
confidence: 99%
“…That is, a significant problem based on the development of chronic CNS electrodes is device failure associated with a fibrotic response mediated by glial cells. 40,58 For overcoming this problem, McKenzie et al 53 focused on the development of novel carbon nanofiber based electrode arrays for CNS neuronal stimulation using compressed carbon nanofibers with reinforcing polycarbonate urethane. The researchers suggested that strong interactions with neurons on carbon nanofibers limited astrocyte (glial scar tissue-forming cells) functions leading to decreased gliotic scar tissue formation.…”
Section: Nanostructured Neural Materialsmentioning
confidence: 99%